Malondialdehyde Levels in Wistar Rat Liver after High Fat Diet and Mango Tea Mistletoe Extract Intake - Putri Maharani Aulia Rakhman; Ari Hayati; Nour Athiroh Abdoes Sjakoer (Biology, Medicine, & Natural Product Chemistry, 2026)
Malondialdehyde (MDA) levels increase due to the accumulation of free radicals that exceed normal limits, leading to oxidative stress. Mango mistletoe and tea mistletoe (MESA-DP) are known to contain secondary metabolites that function as natural antioxidants. The use of antioxidants derived from these mistletoes can serve as an alternative to reduce MDA levels and neutralize free radicals. This study aimed to determine the dose of MESA-DP extract that is more effective in reducing MDA levels. This research employed a Randomized Pre Test–Post Test Control Group design using 35 male Wistar rats (Rattus norvegicus), which were divided into five treatment groups with 4 repetition: G1 normotensive as a control without high fat diet (HFD) and without gavage; G2 as an HFD control without gavage; G3 receiving HFD and MESA-DP of 50 mg/KgBW; G4 receiving HFD and MESA-DP of 100 mg/KgBW; and G5 receiving HFD and MESA-DP of 200 mg/KgBW. Data were analyzed using a one-way analysis of variance (ANOVA) to determine differences in hepatic MDA levels among groups. The results showed significant differences in hepatic MDA. Levels among all treatment groups following administration of MESA-DP extracts. The extracts demonstrated an effect in reducing MDA levels and enhance SOD levels thanks to its antioxidant properties. The most effective doses were found in group G3 50 mg/KgBW with an MDA level of 17,604 ± 0,389.